Impact of butorphanol versus sufentanil on postoperative cognition and inflammation in elderly: a pilot study - Wen, Qiannan; Sun, Defeng; Yang, Lin; Li, Yuexian (Frontiers in Aging Neuroscience, 2024)
Background: This randomized controlled trial aimed to compare the effects of butorphanol and sufentanil on early post-operative cognitive dysfunction (POCD) and systemic inflammation in older surgical patients.: Patients (aged 65 years or above) undergoing surgeries with general anesthesia were randomized to either the butorphanol group (40 μg/kg during anesthesia induction) or the sufentanil group (0.4 μg/kg). Cognitive function changes during the perioperative period were assessed using the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA) scale up to three days after surgery. POCD was defined as a Z-score or composite Z-score greater than 1.96 for both MMSE and MoCA scores. Circulating inflammatory factors, including tumor necrosis factor-alpha (TNF-α), interleukin 1 beta (IL-1β), and interleukin 10 (IL-10), were measured using enzyme-linked immunosorbent assay.The study included 114 patients (median age: 71 years, 57.7% male). Compared to sufentanil, butorphanol significantly reduced the incidence of POCD on the first (11.5% versus 32.7%, P=0.017) and third day (3.8% versus 15.4%, P=0.046) after surgery. Additionally, patients receiving butorphanol had significantly lower circulating levels of TNF-α and IL-1β at the time of discharge from the post-anesthesia care unit and on the first and third day after surgery (P<0.05 for all comparisons). Furthermore, circulating IL-10 levels were significantly higher in patients receiving butorphanol (P<0.05 for all comparisons).Conclusions: Administration of butorphanol during anesthesia induction, as opposed to sufentanil, was associated with a significant reduction in the early incidence of POCD in older surgical patients, possibly attributed to its impact on systemic inflammation.Trial registration: The present study was registered in the China Clinical Trial Center (ChiCTR2300070805, 24/04/2023).